2014
DOI: 10.3389/fpubh.2014.00055
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Endocrine Disrupting Chemicals and Male Reproductive Health

Abstract: Endocrine disrupting chemicals (EDCs) can interfere with normal hormonal balance and may exert adverse consequences on humans. The male reproductive system may be susceptible to the effects of such environmental toxicants. This review discusses the recent progress in scientific data mainly from epidemiology studies on the associations between EDCs and male reproductive health and our understanding of possible mechanisms associated with the effects of EDCs on male reproductive health. Finally, the review provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 105 publications
1
88
0
Order By: Relevance
“…Environmental factors (external and internal factors) like pollutants, global warming and exposure to environmental endocrine disruptors may affect integrity of sperm genome specially the sperm nuclear periphery where DNA is loosely bound to histones in the nuclohistone component (Jeng HA., 2014). Effects may be at different stages of the cell cycle such as during meiosis or spermiogenesis, and such abnormalities can have deleterious effects on offspring (Dinham and Malik, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors (external and internal factors) like pollutants, global warming and exposure to environmental endocrine disruptors may affect integrity of sperm genome specially the sperm nuclear periphery where DNA is loosely bound to histones in the nuclohistone component (Jeng HA., 2014). Effects may be at different stages of the cell cycle such as during meiosis or spermiogenesis, and such abnormalities can have deleterious effects on offspring (Dinham and Malik, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in testicular function is also evident in other studies [23,24,25]. The efects of BPA resemble more or less the estrogenic efects on the testes [18, 26,27] with reduction in daily sperm production [28], deformed acrosomal vesicles, acrosomal caps, acrosomes and nuclei of the spermatids. Tohei et al [29] reported that plasma concentration of testosterone was decreased, and LH was increased in rats after administration of BPA.…”
Section: Efects On Reproductive Systemmentioning
confidence: 52%
“…Sperm DNA integrity represents an essential requirement for the accurate transmission of genetic information. T h e r e i s l i m i t e d a n d c o n t r a d i c t o r y epidemiological evidence on whether endocrine disruptors affect human sperm DNA (14). These contradictions may be due to the different methodologies by which sperm DNA damage was characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine disruptors as defined by the US Environmental Protection Agency, is an exogenous agent that interferes with the production, release, transport, metabolism, binding, action, or elimination of natural hormones in the body responsible for the maintenance of homeostasis and the regulation of developmental processes (11,12). Endocrine disruptors have been reported to decrease the AGD of male and female rats (13), impair sperm chromatin concentration and induce human sperm DNA damage (14). It is however not clear if these DNA damage is transmitted to successive generations.…”
Section: Introductionmentioning
confidence: 99%